Perencanaan Jamban Sehat untuk Rumah Studi Kasus Desa Weninggalih Kabupaten Bogor - Arthono, Andri; Ekadipta, Ekadipta (University of Muhammadiyah Aceh, 2022)
A livable house must meet various requirements, one of which is health requirements, so that the occupants remain healthy. One of the important things that must be in a house is a latrine or bathroom. Inappropriate latrines facilitate the spread of certain diseases such as diarrheal diseases. The planning and manufacture of family latrines must follow the criteria in accordance with existing standards such as layout, water sources, construction, and also the materials. With the existence of family latrines that meet the criteria, a healthy society will be realized, as an effort to implement a healthy lifestyle for the community which was proclaimed by the Ministry of Health as a Clean and Healthy Lifestyle (PHBS). The purpose of this study was to determine the feasibility of sanitation and environmental health in Weninggalih village, Bogor Regency. Methods The research is conducted by conducting a field survey. Data collection is done by visiting the house one by one, where the physical components seen are focused on the bathroom and its supporting facilities. Based on the results of the study, it is known that the houses in the village of Weninggalaih are still very far from being feasible. This can be seen from the construction of the house with earth floors and tends to be humid. In addition, the walls use cubicles that allow air from outside to easily enter, including various small animals, the absence of a low roof, and the absence of a proper bathroom. Therefore, it is recommended to the local authorities to improve the facilities in every resident's house, including making a latrine in each house, constructing drainage channels and also infiltration wells to reduce household waste, including providing space between the house and the animal cages.